A review on parabolic trough/Fresnel based photovoltaic thermal systems. (August 2018) - Kasaeian, Alibakhsh; Tabasi, Sanaz; Ghaderian, Javad; Yousefi, Hossein
Abstract: The concentrating photovoltaic thermal systems are of much interest among all photovoltaic thermal units which have recently been developed. The trough collectors and Fresnel lenses are more significant in case of concentrating devices, and both are the linear parabolic collectors which have been commercialized well. The numerous publications about these collectors show their importance in the efficient cogeneration of heat and power. Therefore, it is interesting to gather and discuss all the related research papers in an article to show the history as well as the latest developments in this field. This study provides a critical review on the trough/Fresnel based photovoltaic thermal systems. The chapters, containing trough and Fresnel lens, are categorized into three parts as experimental, hybrid studies, and analytical-simulation works. With this regard, the experimental works are summarized in individual tables for each mentioned category. To conclude the survey, some gaps are identified, and suggestions are recommended for future works. Highlights: The photovoltaic thermal systems based on trough and Fresnel are reviewed. The chapters include experimental, hybrid, and simulation works. The gaps in the literature are identified for showing other possible research topics. Based on 106 surveyed references, the suggestions are presented for future studies.